SITUASI KEBAHASAAN MASA KINI: KEPUNGAN PENGARUH BUDAYA GLOBAL - Ardianto, Ardianto (Pusat Pengembangan Bahasa IAIN Tulungagung, 2011)
Bahasa Indonesia is a dynamic language. But, the dynamic seems uncontrolled and unregulated which negatively influenced the development of Bahasa Indonesia in future. Further, the disorder of Bahasa Indonesia also reflects the condition of the nation?s culture in which people tend to violent the rules. Therefore, to counter the penetration of negative influence, firstly, the quality of Bahasa Indonesia must be enhanced. This effort can be started from promoting motivation and commitment in using good and correct Bahasa Indonesia in daily communication. Schools and other educational institutions must take part in this effort.